The necessity, logic, and forms of replication - Bettis, Richard A.; Helfat, Constance E.; Shaver, J. Myles (Strategic Management Journal, 2016)
Research summary : A replication study assesses whether the results of a particular prior study can be reproduced, including in new contexts with different data. Replication studies are critical for building a cumulative body of research knowledge. This article discusses and provides a typology of different types of replications, compares replications with other approaches to cumulating knowledge, and provides guidelines toward producing high‐quality replication studies. The articles in this S pecial I ssue provide examples of replication studies in strategic management. Managerial summary : Research studies sometimes draw implications for managerial practice. A single empirical study, however, is specific to a particular context, relies on a particular set of data, and uses a particular research design. As a consequence, a single study cannot establish whether the findings generalize to a different context and whether the research design is robust to alternative approaches. Replication studies can help to establish the range of applicability of prior studies and better support what implications can be drawn for managerial practice . Copyright © 2016 John Wiley & Sons, Ltd.